Impact analysis of composite laminate structures in traditional Jaloe Kayoh boat hulls - Tamlicha, Akram; Samsul Rizal, .; Iskandar, Hasanuddin; Muhamad, Mat Noor; Muhammad, Ikramullah; Muhammad Rizal, .; Nazaruddin, Nazaruddin (Sciendo, 2025)
This study investigates the impact response of a composite laminated structure applied to the hull of a traditional Jaloe Kayoh boat using a glass and ramie-reinforced polyester (GRRP) configuration. The GRRP laminate, which consists of three sequential layers, was engineered to enhance impact resistance in structural marine applications. A series of impact tests were conducted at controlled velocities of 2.4 m/s, 4.4 m/s, 6.4 m/s, 8.4 m/s, and 10.4 m/s, and the results were analysed using both experimental methods and Finite Element Analysis (FEA) simulations. At a baseline impact velocity of 2.4 m/s, experimental strain measurements were closely aligned with FEA predictions, showing a deviation of only 4.7% toward the pendulum impact. However, the strain results in the reverse direction indicated larger discrepancies, highlighting the limitations of predicting asymmetric deformation behaviour. At higher impact velocities, particularly beyond 10.4 m/s, the simulation results revealed that the composite structure begins to approach its elastic threshold, especially on the non-impact (transverse) side, resulting in significantly increased strain levels. The GRRP laminate demonstrated reliable elastic performance in the impact direction, whilst exhibiting vulnerability to transverse deformation under high-energy loading. These findings confirm the effectiveness of the GRRP structure under low-to-moderate impact conditions and suggest the need for reinforcement in the opposite direction, to improve transverse resilience at higher speeds. Overall, this study underscores the value of combining experimental testing and numerical simulations to understand the mechanical behaviour of hybrid composite structures and guide structural design improvements for traditional boat hulls.